2008
DOI: 10.1051/0004-6361:20078793
|View full text |Cite
|
Sign up to set email alerts
|

Polarized NIR and X-ray flares from Sagittarius A*

Abstract: Context. Stellar dynamics indicate the presence of a supermassive 3−4 × 10 6 M black hole at the Galactic Center. It is associated with the variable radio, near-infrared, and X-ray source Sagittarius A* (SgrA*). Aims. The goal is the investigation and understanding of the physical processes responsible for the variable emission from SgrA*. Methods. The observations have been carried out using the NACO adaptive optics (AO) instrument at the European Southern Observatory's Very Large Telescope (July 2005, May 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
169
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(187 citation statements)
references
References 82 publications
18
169
0
Order By: Relevance
“…In addition multi-wavelength observations of flares suggest an adiabatically expanding blob model (Eckart et al 2006a(Eckart et al , 2008Yusef-Zadeh et al 2006a, which can explain the observed time lags between the infrared/X-ray and millimeter flares. However, a general model that provides a quantitative explanation of the frequency-dependent variability of SgrA* in the millimeter and sub-millimeter wavelengths, including the contribution of thermal electrons and relativistic electrons that result in NIR/X-ray flares, is not yet available (see comments in Dexter et al 2010).…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…In addition multi-wavelength observations of flares suggest an adiabatically expanding blob model (Eckart et al 2006a(Eckart et al , 2008Yusef-Zadeh et al 2006a, which can explain the observed time lags between the infrared/X-ray and millimeter flares. However, a general model that provides a quantitative explanation of the frequency-dependent variability of SgrA* in the millimeter and sub-millimeter wavelengths, including the contribution of thermal electrons and relativistic electrons that result in NIR/X-ray flares, is not yet available (see comments in Dexter et al 2010).…”
Section: Introductionmentioning
confidence: 92%
“…With a total bandwidth of about 60 GHz, the system is optimized for the 345 GHz atmospheric window. A detailed description of the LABOCA data recording and analysis in the context of SgrA* is given by e.g., Eckart et al (2008) and Garcia-Marin et al (2011a,b). For completeness, we summarize some of the essentials that are relevant to this paper.…”
Section: The Sub-millimeter Datamentioning
confidence: 99%
See 3 more Smart Citations